READINESS FOR HALAL CERTIFICATION SUBMISSION IN COFFEE SMALL AND MEDIUM ENTERPRISES (SMES): A CASE STUDY OF HOUSE OF COFFEE BY SPEEDTERIA, CIMAHI - Mumtaz, Muhammad Daffin Salman; Wiyono, Sulistyodewi Nur (Buletin Ilmiah Impas, 2025)
The implementation of halal certification for MSMEs in Indonesia is regulated by Law No. 33 of 2014, which mandates that MSMEs obtain halal certification. House of Coffee by Speedteria, a coffee shop located in Cimahi, has not yet obtained halal certification. This study aims to analyze consumer characteristics, their perceptions of halal products, the company’s readiness to apply for halal certification, identify the criteria considered in preparing for certification, and determine alternative actions that can support the process. This research uses a quantitative approach with a case study technique and AHP analysis tools, focusing on consumer characteristics, perceptions of halal products, key criteria for halal certification readiness, and relevant alternative strategies. Respondents were selected using convenience sampling, based on ease of access and willingness to participate in interviews. The results show that the majority of consumers are teenagers who consider the halal label important to be clearly displayed and express a desire for halal certification on coffee beverage products. House of Coffee by Speedteria is assessed to have a fairly good level of readiness for the halal certification process. Information is identified as the main criterion in preparation, while the prioritized alternative actions include hiring a legal officer and improving quality control standards in accordance with the halal system.